FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU ORANG TUA DALAM MELAKUKAN KEKERASAN VERBAL TERHADAP ANAK USIA PRA-SEKOLAH - Fitriana, Yuni; Pratiwi, Kurniasari; Sutanto, Andina Vita (Jurnal Psikologi, 2015)
Verbal abuse in children is all forms of greeting parents to children who are threatening, scaring, and insulting. This happens every day at home should be the safest place and refuge for children. Economic, social, employment, lack of knowledge to educate children and parents lack understanding of religion contributing cause parents do violence on their children. Parents commit verbal violence as a way to educate children is naughty and not obedient, so it is necessary to study in order to know the factors related to the behavior of parents in verbal violence against children pre-school age. Quantitative research methods with descriptive analytic approach. The research sample 76 people, with a proportionate random sampling technique. Instrument questionnaire. The research variables include variables such as age, education, economics, attitudes, knowledge, experience, environment, and the dependent variable is the verbal violent behavior. The analysis of univariate and bivariate data using chi square test. Results of this study there was no correlation with the behavior of a parent education did verbally abuse her son (p = .767), there is no economic relationship with the parents' behavior on their verbal violence (p = .248), there is a correlation between age of knowledge, attitude, experience and the environment there is a relationship with the parents' behavior on their verbal violence (p < 0,001).